Menopause and Sleep Apnea. (June 2019) - Perger, Elisa; Mattaliano, Paola; Lombardi, Carolina
Highlights: Specific individual evaluations, including of menopausal status, are needed to better characterize sleep-related breathing disorders. Specific individual evaluations, including of menopausal status, are needed to optimize early treatment The mechanisms through which menopause may influence the development of obstructive sleep apnea are not fully understood. Present work in focused on sleep-related breathing disorders and gender, in particular exploring the potential role of menopausal status. Abstract: Obstructive sleep apnea (OSA) is a chronic and common adult disorder characterized by recurrent episodes of upper-airway obstruction and reopening during sleep. OSA is associated with intermittent hypoxia, sympathetic overactivity, oxidative stress and high cardiovascular mortality and morbidity. It is known to be more common in men than women, partly due to differences in anatomy and functional respiratory components. There are also gender differences in reported symptoms, leading to potential under-diagnosis in females. This gender difference tends to decrease after menopause, demonstrating a role of menopausal status itself in OSA phenotypes. Aging, fat mass distribution, sex hormones and upper-airway collapsibility are postulated to play a major role in these findings. This review focuses on the most recent studies exploring gender differences in the prevalence, pathogenesis and clinical features of OSA. It discusses the role of menopause in this, and explore the underlying pathophysiological mechanisms.